2017
DOI: 10.1002/mrd.22834
|View full text |Cite
|
Sign up to set email alerts
|

Sperm capacitation pretreatment positively impacts bovine intracytoplasmic sperm injection

Abstract: The efficiency of intracytoplasmic sperm injection (ICSI) in bovines is low compared to other species due in part to inadequate egg activation and sperm nucleus decondensation after injection. We hypothesized that this low efficiency is due to the lack of complete sperm capacitation, so we evaluated the effects of isobutylmethylxanthine (IBMX) and methyl-β-cyclodextrin (MβCD) on bovine sperm capacitation and on the preimplantation developmental potential of bovine embryos generated by ICSI. Treatment with IBMX… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 99 publications
0
12
0
Order By: Relevance
“…Additionally, we also observed a significant increase in tyrosine phosphorylation levels under these conditions both in Whitten's and HTF media. Merocyanine 540 has been previously used in boar (Harrison & Miller, ), dog (Steckler et al, ) and bovine sperm (Aguila et al, ) as an indicator of plasma membrane destabilization, because it binds to the segments of the plasma membrane that are in a higher state of lipid disorder (Langner & Hui, ; Leahy & Gadella, ; Williamson et al, ), indicating that changes in the membrane architecture related to sperm capacitation have initiated. These changes apparently result from cholesterol efflux supporting the addition of cholesterol acceptors such as BSA, which are normally included in the capacitation media.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, we also observed a significant increase in tyrosine phosphorylation levels under these conditions both in Whitten's and HTF media. Merocyanine 540 has been previously used in boar (Harrison & Miller, ), dog (Steckler et al, ) and bovine sperm (Aguila et al, ) as an indicator of plasma membrane destabilization, because it binds to the segments of the plasma membrane that are in a higher state of lipid disorder (Langner & Hui, ; Leahy & Gadella, ; Williamson et al, ), indicating that changes in the membrane architecture related to sperm capacitation have initiated. These changes apparently result from cholesterol efflux supporting the addition of cholesterol acceptors such as BSA, which are normally included in the capacitation media.…”
Section: Discussionmentioning
confidence: 99%
“…Membrane fluidity, as an early capacitation event, was evaluated using the merocyanine assay (MC540, M6390). MC540 is a hydrophobic dye that stains cell membranes more intensely if their lipid components are in a higher state of disorder (Rathi et al, ) and has been used in dog (Steckler, Stout, Durandt, & Nothling, ), bovine (Aguila, Zambrano, Arias, & Felmer, ) and equine sperm (Ortgies et al, ; Rathi et al, ). Briefly, 5 μl of MC540 (270 μM stock solution) and 2 μl of SYTOX green (20 μM stock solution, Molecular Probes, Eugene, OR, USA) were added to the sperm suspension (2 × 10 6 sperm/ml) and incubated for 30 min at 38.5°C in air and darkness ( n = 3 replicates for each stallion).…”
Section: Methodsmentioning
confidence: 99%
“…Hyperactivation and protein tyrosine phosphorylation rises are the best characterized features of sperm capacitation, so advances in the understanding of in vitro capacitation after SU and DGC may help to improve the efficacy and success in ART. Indeed, it has been shown that bovine intracytoplasmic sperm injections using spermatozoa recovered by DGC and pre-incubated under capacitating conditions promote pronucleus formation rate and blastocyst rate [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…The difficulty in remodeling the male chromatin following sperm injection is not unique to the bovine, as earlier studies noted impaired and asynchronous chromatin remodeling following ICSI in the mouse (Shoukir et al 1998, Ajduk et al 2006), pig (Kren et al 2003, Lee et al 2003, Nakai et al 2011) and humans (Dozortsev et al 1994, Sousa & Tesarik 1994, Flaherty et al 1995). Several common factors have been suggested to hinder the remodeling of injected sperm, such as the lack of capacitation and acrosome reaction (Sekhavati et al 2012, Zambrano et al 2016, Aguila et al 2017). Nevertheless, unique features of the bovine spermatozoa may further complicate PN formation in this species.…”
Section: Discussionmentioning
confidence: 99%